Avaliação da atividade tricomonicida do derivado clorado do metronidazolsobre cepa sensível e resistente de Trichomonas vaginalis - Michelle de Oliveira Chacon (2016)
The Trichomonas vaginalis is the etiologic agent of the most common non-viral sexually transmitted disease (STD) in the world, the trichomoniasis. This disease has been associated with other STDs, evidencing an important co-factor for the transmission and acquisition ofthe Human Immunodeficiency Virus. The metronidazole (MTZ) is currently the most used drug in the treatment of trichomoniasis. However, its usage is inappropriate with administrations at sub-therapeutics levels, usually prescribed as prophylaxis, and might support the emergence of resistance. Refractory cases of treatment have been described andconstitute an important barrier to the success of the treatment, not only for trichomoniasis, but also for other infectious diseases, mainly considering the lack of therapeutic options. In contrast, it is suggested the increase of the MTZ therapeutic doses, even though the higher doses might lead to severe collateral effects, making the usage intolerable in some cases. In the search for treatments with more potent and less toxic molecules, the chlorine analogous of MTZ (MTZ-Cl) was synthesized and tested. In vitro inhibitions assays exhibited interesting results compared to MTZ, showing IC50 up to 11-fold lower than the precursor molecule for T. vaginalis sensitive and MTZ-resistant strains. The safety of MTZ-Cl was evaluated by cytotoxic assay in hepatic cells, and acute toxicity in rodents. In vitro assay did not indicate any toxicity. In vivo analyses revealed a small hepatic alteration in one of the animals treated with MTZ-Cl, but other differences between this molecule and its precursor was not observed. There were no deaths among the treated animals, thus the LD50 was not possible to be determined. Considering that the dose used during the test with MTZ was much higher than the recommended for the treatment of trichomoniasis, and extrapolating this analysis to MTZCl, it is noteworthy that the dose used during the test is even more significant, since this is a more potent molecule. Thereby we can speculate that the toxic concentrations of MTZ-Cl far exceed those potentially therapeutics. Differences in the action of both drugs were evaluated by the formation of cytotoxic free radicals, where there was a higher formation of free radicals in the parasites treated with MTZ-Cl. Our results indicate a great potential of MTZ-Cl as a trichomonicidal therapy, and a promising alternative for further clinical trials.